Challenges and support for quality of life of youths living with HIV/AIDS in schools and larger community in East Africa: a systematic review - Emmanuel Kimera; Sofie Vindevogel; Jessica De Maeyer; Didier Reynaert; Anne-Mie Engelen; Fred Nuwaha; John Rubaihayo; Johan Bilsen (Systematic Reviews, 2019)
Abstract Background Youths living with HIV/AIDS (YLWHA) experience innumerable challenges within schools and the larger community. Nonetheless, these environments are potential sources of support for such youths. This review provides a synthesis of evidence about these challenges and support available for YLWHA to inform the design and implementation of interventions that support the wellbeing of youths living with HIV/AIDS in an East African context. Methods We searched MEDLINE, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Web of Science, and Cochrane central registry of systematic reviews and randomized control trials for studies conducted in East Africa and published in English in the last 10 years (March 2007 to March 2017). We also searched Google Scholar and reference lists of all included studies. We purposed to include both qualitative and quantitative data but no quantitative data merited inclusion. We analyzed qualitative data using a framework thematic analysis. Results We included 16 primary studies conducted in clinic and community settings that used qualitative or mixed methods. Three overarching themes—psychosocial wellbeing, treatment and health, and disclosure of HIV status together with a sub-theme of stigma that was important across the three overarching themes—were the basis for analysis. In each overarching theme, a duality of challenges versus support was reported. Psychosocial wellbeing included subthemes of challenges in schools and larger community, financial challenges, domestic violence, sexual and reproductive health challenges, and psychosocial support. Conclusion YLWHA experience numerous challenges and support needs, some of which occur in schools and affect their QoL. The effects of these challenges are poor health and educational outcomes as well as school dropout. The schools in which youths spend most of their formative years have not provided adequate support for YLWHA. This review identified that although most of the challenges that studies identified arose from within schools and that a few supportive approaches were available, none of the studies explored how these supportive approaches would work in schools. It was additionally identified that stigma complicates challenges of living with HIV/AIDS necessitating interventions for the wellbeing of YLWHA to understand and address HIV-stigma and its ramifications. Such interventions ought to be sustainable in schools, culturally appropriate, and multidisciplinary in order to promote the general health of all students.